Evaluating the Effectiveness of Food Safety Policies in Portugal: A Stakeholder-Based Analysis of Challenges and Opportunities for Food Safety Governance - Júlia Rodrigues; Cristina Saraiva; Juan García-Díez; José Castro; Alexandra Esteves (Foods)
Food safety is a fundamental component of public health, economic stability, and consumer confidence. In Portugal, the National Integrated Multiannual Control Plan (NIMCP) serves as a strategic framework for ensuring food safety and compliance with European Union food regulations. However, challenges persist in policy implementation and enforcement, as well as in stakeholder engagement, which impact the effectiveness of food safety governance. This study employs a mixed-methods approach to assess stakeholder perceptions of the NIMCP, focusing on levels of compliance, barriers to its implementation, and potential improvement measures. A structured online survey was conducted with 217 stakeholders, including representatives of public institutions, private entities, associations, and consumer groups. The survey assessed the perceived importance of the NIMCP objectives and levels of compliance and identified barriers, such as a lack of communication between public entities, the dispersion of responsible agencies, and insufficient dissemination of information. The results indicate that stakeholders perceive a satisfactory level of compliance with the NIMCP objectives, especially in areas such as animal health and risk control. However, challenges persist in ensuring plant health and implementing official controls. Furthermore, stakeholders highlight systemic inefficiencies and resource constraints. The main barriers include fragmented governance structures, limited inter-agency collaboration, and insufficient professional training. Stakeholders proposed various improvement measures, emphasizing the need for better coordination, planning, and communication, including awareness campaigns for operators, the creation of an integrated IT network, and the development of training programs. The Analytical Hierarchy Process (AHP) revealed that risk control and consumer protection are top priorities for all stakeholder groups, while plant and animal health receive lower priority. The study concludes that while the NIMCP is generally perceived as effective, addressing systemic issues such as coordination, communication, and resource allocation is essential to improving food safety governance. Policymakers are encouraged to adopt a more structured and integrated approach to improve implementation of the NIMCP, ultimately strengthening public health protection and consumer confidence in the food supply chain.